2023
DOI: 10.1186/s13756-023-01216-0
|View full text |Cite
|
Sign up to set email alerts
|

Molecular surveillance reveals widespread colonisation by carbapenemase and extended spectrum beta-lactamase producing organisms in neonatal units in Kenya and Nigeria

Abstract: Objectives Neonatal sepsis, a major cause of death amongst infants in sub-Saharan Africa, is often gut derived. Gut colonisation by Enterobacteriaceae producing extended spectrum beta-lactamase (ESBL) or carbapenemase enzymes can lead to antimicrobial-resistant (AMR) or untreatable infections. We sought to explore the rates of colonisation by ESBL or carbapenemase producers in two neonatal units (NNUs) in West and East Africa. Methods Stool and rec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…In a 2023 study that also included Kenya, 20/24 Nigerian infants presented CPE colonization at some point during hospital admission. bla NDM was identified especially, but bla OXA-48 and bla VIM were also identified [22]. More noteworthy recent data were found in a study on Sub-Saharan countries described below [116].…”
Section: Resultsmentioning
confidence: 74%
See 2 more Smart Citations
“…In a 2023 study that also included Kenya, 20/24 Nigerian infants presented CPE colonization at some point during hospital admission. bla NDM was identified especially, but bla OXA-48 and bla VIM were also identified [22]. More noteworthy recent data were found in a study on Sub-Saharan countries described below [116].…”
Section: Resultsmentioning
confidence: 74%
“…Seven of eighteen (7/18) Kenyan infants tested positive for CPE colonization at some point during admission. The most prevalent gene was bla NDM , but bla OXA-48 and bla VIM were also identified [22].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this prospective study, it was revealed that upon admission to the HIMFG NICU, 27.6% (13/47) of patients were already colonized by ESBL-PEco and ESBL-PKpn. The percentage increased to 87% (41/47) by the end of the follow-up period, exceeding the reporting range, which typically ranged from 8% to 83% (Huerta-Garcıá et al, 2015;Folgori et al, 2018;Hagel et al, 2019;Edwards et al, 2023). Notably, the study by Huerta-Garcıá et al carried out in our country reported that during the second week of hospital stay, 81% of neonates were intestinally colonized by ESBL-PEco and ESBL-PKpn, while our study revealed 78.7% (37/47) colonization during the same week of hospitalization (Huerta-Garcıá et al, 2015).…”
Section: Discussionmentioning
confidence: 86%
“…Gastrointestinal carriage of AMR bacteria may precede infection and, without active surveillance, can serve as a hidden reservoir for drug-resistant organisms' transmission in hospital environments [11] [12] [13]. Yet, few studies have focused on faecal carriage of MDR bacteria and risk factors for colonization in Kenya, including faecal carriage of CRE in adults and children (1%) [14], carbapenemase-producing organisms (62.4%) in hospitalized newborns [15], and ESBL Enterobacteriales among neonates before (10%) and after admission (55%) [13]. Some identi ed risk factors for colonization with antimicrobial-resistant bacteria are eating soil from the household yard, informal hand-washing stations [16], number of known carriers and participants in a ward [13].…”
Section: Introductionmentioning
confidence: 99%